Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/plants10020291
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Changes during the Upward Expansion of Deyeuxia angustifolia Kom. in the Alpine Tundra of the Changbai Mountains, China

Abstract: Ecological adaptation plays an important role in the process of plant expansion, and genetics and epigenetics are important in the process of plant adaptation. In this study, genetic and epigenetic analyses and soil properties were performed on D. angustifolia of 17 populations, which were selected in the tundra zone on the western slope of the Changbai Mountains. Our results showed that the levels of genetic and epigenetic diversity of D. angustifolia were relatively low, and the main variation occurred among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Epigenetic changes are closely related to climatic factors such as temperature [ 31 , 33 , 81 ] and precipitation [ 31 , 33 ]. Epigenetic changes are also found to be closely associated with ecological factors such as soil factors [ 31 , 82 ], NDVI, and PET [ 31 , 33 ]. Topographic variables including slope and aspect are also found to be closely related to epigenetic changes [ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic changes are closely related to climatic factors such as temperature [ 31 , 33 , 81 ] and precipitation [ 31 , 33 ]. Epigenetic changes are also found to be closely associated with ecological factors such as soil factors [ 31 , 82 ], NDVI, and PET [ 31 , 33 ]. Topographic variables including slope and aspect are also found to be closely related to epigenetic changes [ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…All these factors make alpine habitats a fragile ecosystem, ideal for studying the effect of the environment on epigenomes. Many studies in alpine plants have indicated that epigenetic modifications play an important role in the adaptive response to climatic changes and local adaptations ( Wu et al, 2013 ; Zhao et al, 2014 ; Nicotra et al, 2015 ; Song et al, 2015 ; Alakärppä et al, 2018 ; Schinkel et al, 2020 ; Ni et al, 2021 ) ( Table 1 ). Further, studies have also revealed interesting observations of epigenetic regulation of fitness and adaptability of populations in ecological communities like grasslands ( Herrera and Bazaga, 2010 ), temperate deciduous forests ( Avramidou et al, 2015 ; Gugger et al, 2016 ; Ahn et al, 2017 ; Vanden Broeck et al, 2018 ) and communities from colder continental and Mediterranean climates ( Saéz-Laguna et al, 2014 ) ( Table 1 ).…”
Section: Underpinning Of Epigenetic Adaptive Responses In Natural Pop...mentioning
confidence: 99%